COMMUNITY PREPAREDNESS TO FACE THE ERUPTION OF MOUNT KERINCI IN THE VILLAGE OF KERSIK TUO KAYU ARO SUB-DISTRICT OF KERINCI REGENCY - Sandra, Riko - (STKIP PGRI Sumbar, 2014)
This research was conducted in the of Kerinci regency, which aims to determine the community preparedness to face the eruption of Mount Kerinci, in terms of: (1) society knowledge, (2) community participation, and (3)Availability of facities for,. This research is descriptive research with 70 households in the village of kersik tuo grit. Data collection through observation and pacification questionnaire, of the sample responden. The data analysis performed by analyzing the percentage of community preparedness. The study found: (1) From the aspect of the society knowledge ,the society is well enough in preparedness eruption of Mount Kerinci. (2) From the aspect of community participation,is good in the eruption of Mount Kerinci preparedness. (3) The availability of facilaties evacuation are not well established in the eruption of Mount Kerinci preparedness.